An Assessment of the Hypoglycemic and Antioxidant Properties of the Methanol Extract of Erythrophleum guineense Stem Bark in Albino Rats. Issue 4 (2nd October 2022) - Akande, Motunrayo Ganiyat; Nwinyi, Florence Chimezie; Egua, Maxwell Osaronowen; Ode, Julius Okwoche; Onakpa, Michael Monday; Mikail, Hudu Garba; Onoja, Samuel Okwudili; Mohammed, Adamu; Akumka, David Dezi
ABSTRACT: Erythrophleum guineense G. Don is an enormous shade species that is indigenous to moist regions of Africa. Various forms of its bark are used to treat heart diseases, edema, headache, and body pains. In this study, the stem bark of Erythrophleum guineense was subjected to double maceration and extracted with 80% methanol. The methanol extract was screened for its phytochemical components and in vitro antioxidant activity through the utilization of the Ferric Reducing/Antioxidant Power (FRAP) and 1, 1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging activity procedures. The acute toxicity of the plant extract was evaluated using Lorke's method in albino rats. Screening was conducted in normoglycemic and glucose-challenged albino rats to determine the plant extract's control of blood glucose levels. The doses of the methanol extract of Erythrophleum guineense tested in rats through the oral route were 100, 200, and 400 mg kg −1 body weights of the rats. The effects were compared with glibenclamide (0.2 mg kg −1 per os) and normal saline. The phytochemical constituents of the methanol extract of Erythrophleum guineense were saponins, terpenes, tannins, steroids, carbohydrates, and alkaloids. The results indicated that the plant extract possessed antioxidant and hypoglycemic properties. Further research is warranted to isolate the active hypoglycemic principle of the stem bark of Erythrophleum guineense .